A mediação de leitura para crianças do candomblé: uma contribuição ao incentivo a leitura - Araujo, Leonardo Silva de (2023)
The present research aims to investigate the importance of reading mediation in spaces of liturgical cults of Afro-Brazilian religions. To analyze the contribution of reading in the valorization of the people of terreiro and their beliefs, seeking to demonstrate through reading an effective tool in the construction of an identity through stories that report the trajectory of their ancestors. To ask the importance of reading in relation to the perpetuation of the cult of Afro-Brazilian religions through reading mediation, in addition to encouraging education, being reading a precursor to keep alive their histories, memories and culture. To investigate the main actors responsible for reading mediation within these sacred spaces, in the formation and identity construction of children of terreiros regarding their liturgy, report the formation of this identity as a way to combat racism and ethnic and religious prejudices in force in Brazilian society.